Monitoring Goat Feeders Using IoT (Internet of Things) Technology - Muhammad Syahputra Novelan (Jurnal Info Sains : Informatika dan Sains, 2023)
Goat confine cultivating as of now has awesome potential. While running a goat ranch, mistakes frequently happen in booking animal feed and estimating the heaviness of feed to give programmed feed progressively as per the predefined time. "IoT (Internet of Things) Based Goat Feeding Technology Innovation by Using Smartphones to Increase Farmer Performance Efficiency" will be researched and produced by the author. This innovation is planned utilizing NodeMCU which is associated with a servo engine and 4 divert hand-off in every goat pen and can naturally compute the heaviness of feed for every goat which has been changed in accordance with the weight per goat. The techniques utilized in this examination include: data collection on partner goat farms, data analysis, online literature searches for the research process and various journals, data collection, efficiency evaluation of tool performance, and tool design and testing. The findings of this study indicate that this technology can be controlled online, or through what is typically referred to as an IoT (Internet of Things) system. As a result, partners can enjoy a number of advantages, including time savings, simple monitoring, a decrease in goat mortality rates, and stable growth.